Seasonal Changes of Organic Carbon Mixing, Degradation and Deposition in Yangtze River Dominated Margin Related to Intrinsic Molecular and External Environmental Factors. Issue 12 (13th December 2021) - Han, Lulu; Wang, Yinghui; Xiao, Wenjie; Wu, Jianqiang; Guo, Lixia; Wang, Yasong; Ge, Huangmin; Xu, Yunping
Abstract: The East Asian monsoon is characterized by warm, humid summer and cool, dry winter that results in seasonal changes in fluvial sediment and organic carbon (OC) discharge. Here, we report measurements of elemental, isotopic, and optical compositions of OC in surface waters and sediments that were collected along the lower Yangtze River, Estuary, and East China Sea continuum in March and July 2019. The principal component analysis separates samples into three groups that correspond to fresh water area, mixing area, and seawater area. The terrigenous signal in the mixing area, indicated by water salinity and δ 13 C, is stronger in July. The applications of binary mixing models based on water salinity, dissolved OC (DOC) concentration and specific terrigenous fluorescence component suggest: (a) net removal of DOC from waters in July, but net addition of DOC into waters in March, attributed to more extensive degradation and larger deposition of OC in summer; and (b) more conservative behaviors of terrigenous OC compared to marine or mixed OC, suggesting an important role of intrinsic molecular characteristics on the persistence of DOC. The estimated monthly OC burial flux in the estuary and continent shelf is 0.48 × 10 12 g in July and 0.081 × 10 12 g of OC in March, equal to 15.5% and 2.6% of the annual OC discharge by the Yangtze River, respectively. Our study suggests that the burial of OC mainly occurs in the summer monsoon due to the larger sediment load of the Yangtze River, prevailing southeastern wind, and intensified Kuroshio Current. Plain Language Summary: Large rivers export an enormous amount of terrigenous sediment and carbon into the ocean. Under the combined influence of rapid climate change and intense human disturbance, the carbon cycling in estuaries and adjacent seas is highly dynamic. Here, we examine elemental, isotopic, and optical characteristics of organic carbon in waters and sediments along the Yangtze River, Estuary, and East China Sea continuum, and compare organic carbon concentration, composition, and deposition between March and July of 2019, corresponding to normal and high‐water discharge, respectively. We have obtained three key findings of the transport, mixing, and deposition processes of organic carbon in this large river‐dominated margin. (a) There is a net removal of organic carbon from waters in July, and net addition of organic carbon into waters in March. (b) Terrigenous dissolved organic carbon is more conservative than aquatic/marine dissolved organic carbon. (c) The organic carbon burial flux in the estuary and shelf sea is 0.48 × 10 12 g in July, five‐fold greater than that in March (0.081 × 10 12 g). Thus, the accumulation of organic carbon mainly occurs in the summer monsoon mainly attributed to the larger sediment load of the Yangtze River, prevailing southeastern wind, and intensified Kuroshio Current. Key Points: Terrigenous dissolved organic carbon (DOC) is more conservative than aquatic/marine DOC during seaward transport and mixing processes There is net removal of DOC in July and net addition of DOC in March in the Yangtze River estuary and shelf The OC burial in the Yangtze River estuary and shelf in July is five‐fold greater than that in March